Peace and democracy in Suriname : final report of the Special Mission to Suriname (1992-2000) (OAS WashingtonUS, 2001)
Covers the activities of the OAS Special Mission to Suriname. Focuses on the major events and themes of Suriname's history and political experiences.
Keywords: DEMOCRACY